THE HOLODOMOR OF 1932-1933 IN UKRAINE (ACCORDING TO THE DOCUMENTS OF SKOROPADSKYI’S ARCHIVE IN THE CENTRAL STATE HISTORICAL ARCHIVE OF UKRAINE) - KUGAI, Vitalii (Київський національний університет імені Тараса Шевченка, 2023)
The article analyzes an unknown body of documents on the history of the Holodomor in Ukraine in 1932-1933, preserved in the Skoropadskyi Fund - the archive of the family of the last hetman of Ukraine, Pavlo Skoropadskyi. For a long time, this archive was kept in the private property of P. Skoropadsky's daughter YElizaveta Skoropadska, and later in the East European Institute named after V. Lipinsky in Philadelphia (USA). In 2006, the archive was sent to the Central State Historical Archive of Ukraine (Kyiv), where it was at the stage of scientific and technical development and became available to researchers only at the end of 2022. Documents on the history of the Holodomor were deposited in the fund thanks to YE. Skoropadska, who from 1933 headed the Committee for Aid to the Starving in Ukraine, which provided material aid to the victims of the famine in Ukraine, conducted organizational work to collect funds for the starving, and disseminated information about this famine in the world. The archive of E. Skoropadska includes hundreds of documents with a total volume of more than 6,300 sheets. This is the largest archive of documents about the Holodomor of 1932-1933 in Ukraine and the world. It contains letters from witnesses of the Holodomor, testimonies of various people, articles, clippings from newspapers and magazines, etc. The article concludes that the analyzed documents indisputably prove the artificial nature of the famine of 1932-1933, which was planned and carried out by the communist regime of the USSR and became a terrible crime against the Ukrainian people. During the Holodomor in Ukraine and the Kuban, where mostly representatives of the Ukrainian ethnic group lived, whole villages died and millions of people died. The collection of archival documents by YE. Skoropadska about the Holodomor of 1932-1933 in Ukraine is unique for Ukrainian historical science. These materials are the most complete, integral and voluminous body of documents collected "on hot tracks", which have no analogues in Ukraine and the world.

У статті аналізується невідомий корпус документів з історії Голодомору в Україні 1932-1933 років, що збереглися у фонді Скоропадських - архіві родини останнього гетьмана України Павла Скоропадського. Тривалий час цей архів зберігався у приватній власності дочки П. Скоропадського Єлизавети Скоропадської, а згодом у Східноєвропейському інституті ім. В. Липинського у м. Філадельфія (США). У 2006 р. архів надійшов до ЦДІАК України, де перебував на стадії науково-технічного опрацювання і тільки наприкінці 2022 р. став доступним для дослідників. Документи з історії Голодомору відклалися у фонді завдяки Є. Скоропадській, яка з 1933 р. очолювала Комітет допомоги голодуючим в Україні, що надавав матеріальну допомогу жертвам голоду в Україні, провадив організаційну роботу зі збору коштів для голодуючих та розповсюджував інформацію про цей голод у світі. В архіві Є. Скоропадської нараховуються сотні документів загальним обсягом понад 6300 аркушів. Це найбільший в Україні і світі архів документів про Голодомор 1932 – 1933 рр. в Україні. У ньому містяться листи свідків Голодомору, свідчення різних осіб, статті, вирізки з газет та часописів тощо. У статті робиться висновок, що аналізовані документи беззаперечно засвідчують штучний характер голоду 1932 – 1933 рр., який був спланований і здійснений комуністичним режимом СССР і став жахливим злочином проти українського народу. Упродовж Голодомору в Україні й на Кубані, де переважно жили представники українського етносу, вимирали цілі села та помирали мільйони людей. Зібрання архівних документів Є. Скоропадської про Голодомор 1932–1933 рр. в Україні є унікальним для української історичної науки. Ці матеріали є найбільш повним, цілісним і об’ємним корпусом документів, зібраних «по гарячих слідах», яким немає аналогів в Україні і світі.
ГОЛОДОМОР 1932-1933 РР. В УКРАЇНІ (ЗА ДОКУМЕНТАМИ АРХІВУ СКОРОПАДСЬКИХ В ЦДІАК УКРАЇНИ)
Keywords: The Holodomor of 1932-1933 in Ukraine; Skoropadski; Central State Historical Archive of Ukraine (Kyiv); Голодомор 1932-1933 рр. в Україні; Скоропадські; ЦДІАК України